Original papersThe role of insulin-like growth factor-1 in development of coronary no-reflow and severity of coronary artery disease in patients with acute myocardial infarction - Akturk, Ibrahim Faruk; Yalcin, Ahmet Arif; Biyik, Ismail; Caglar, Nihan Turhan; Isiksacan, Nilgun; Sarikamis, Cetin; Uzun, Fatih; Celik, Omer; Caglar, Ilker Murat (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction : Insulin-like growth factor-1 (IGF-1) has atheroprotective effects via reduction in oxidative stress, cellular apoptosis, pro-inflammatory signaling, and endothelial dysfunction. Aim : We hypothesized that low levels of IGF-1 may be associated with the severity and extent of coronary artery disease and development of the coronary no-reflow phenomenon in patients with acute ST-elevation myocardial infarction (STEMI) and investigated the role of the IGF-1 molecule in the coronary no-reflow phenomenon and severity of coronary artery disease (CAD) in patients with acute STEMI in a tertiary hospital. Material and methods : The study was conducted among 113 patients undergoing primary percutaneous coronary intervention (PPCI) for STEMI, of whom 49 patients developed the no-reflow phenomenon. Coronary no-reflow was defined as Thrombolysis In Myocardial Infarction (TIMI) flow grade 2 or less after intervention. Insulin-like growth factor-1 levels were measured in both groups. The severity and extent of CAD were evaluated according to the Gensini and Syntax scores. Results : Although IGF-1 levels were lower in the no-reflow group, there was not a statistically significant difference between the no-reflow group and the control group (116.65 ±51.72 vs. 130.82 ±48.76, p = 0.130). Gensini and Syntax scores were higher in the no-reflow group. There was no association between Gensini and Syntax scores and IGF-1 levels (r = –0.071, r = 0.479, r = –0.158, p = 0.113). Conclusions : In this study, IGF-1 levels were not statistically different between patients developing the no-reflow phenomenon and controls. There was no association between development of the no-reflow phenomenon and severity of CAD or IGF-1 levels. Nevertheless, large scale studies are needed to verify these results.